Anisotropic microstructural evolution and coarsening in free sintering and constrained sintering of metal film by using FIB-SEM tomography. (15th August 2021) - Okuma, Gaku; Miyaki, Ryo; Shinobe, Kan; Sciazko, Anna; Shimura, Takaaki; Yan, Zilin; Hara, Shotaro; Ogashiwa, Toshinori; Shikazono, Naoki; Wakai, Fumihiro
Abstract: The anisotropic microstructure develops during powder processing and constrained sintering. FIB-SEM tomography was used to investigate the microstructural evolutions of Au submicron particles during free sintering and constrained sintering. The decrease in total surface area and the coarsening, i.e. the increase of mean intercept length of solid phase, were observed during the densification process. The anisotropic packing structure of spherical particles induced by casting process was characterized by area weighted fabric tensor, which represented the bond orientation and the anisotropy of contact area. In free sintering, the initial anisotropy in packing structure decreased with densification. In constrained sintering, the initial anisotropy observed by the mean intercept length of pore was reversed in the later stage. The microstructure evolved so as to form the elongated pores along the thickness direction. An open pore structure model was presented to explain the microstructural evolution in the intermediate stage. Graphic abstract: Image, graphical abstract